Efficient market theory on trial: The case of PT Semen Indonesia - Doloksaribu, Raja Pranatha; Maharani, Arum Puspita; Qadri, Resi Ariyasa (PT WIM Solusi Prima, 2025)
This study seeks to investigate the dynamics within PT Semen Indonesia (Persero) Tbk, particularly examining the paradox of its share price decline during a period of favorable operational and financial performance from November 2022 to May 2023. Employing both interviews with high-level executives and extensive literature review, the research adopts a mixed-method approach. Interview data were meticulously analyzed using clustered coding to draw nuanced insights, while the literature review served to contextualize and bolster the analysis of the empirical data. The findings indicate that despite the robust operational and financial health of PT Semen Indonesia during the specified period, the company experienced a concomitant decline in its stock value, challenging the assumptions of the Efficient Market Theory. The disparity between the company’s performance metrics and its stock price behavior suggests a weak application or potential invalidity of the Efficient Market Theory in this instance. This research not only underscores the complexities of stock price determinations within Indonesian state-owned enterprises but also opens avenues for future studies to explore similar phenomena across different firms or industries. The unique insights gained from high-level sources within the company provide a valuable foundation for further scholarly inquiry into market efficiency theories.